Pelatihan dan Pendampingan Strategi Branding Produk bagi UMKM di Kelurahan Gununganyar Kota Surabaya - Janah, Yeni Khoirotul; Diana, Laksmi; Pramudyawardhani, Mahadevi (LPPPM STAI Darul Hikmah Bangkalan, 2022)
Branding training and mentoring activities were carried out in Gununganyar District, Surabaya City. This activity is in the form of training and direct assistance for MSMEs. This training and mentoring activity combines aspects that can be used to support the branding process, such as packaging and labeling, product photography, and e-commerce. The initial stage in this activity is to know the obstacles and efforts that have been made by MSME actors. Then proceed with the process of socialization and training in the form of theory and practice and then carry out branding assistance directly at MSME locations. Based on the activities that have been carried out, several MSMEs can be encouraged to improve branding and develop their creativity so as to update product packaging designs and expand online sales. In its implementation, this activity received a positive response from both the community and village officials as partners, seen from the amount of enthusiasm and support given during the activity. The results of this activity are expected to be able to encourage the level of economy and creative entrepreneurial activities in Gununganyar District which in the end will also be able to have an influence on the process of empowering human resources.